Interaction between phosphoprotein and nucleocapsid of newcastle disease virus - Ahmad Raus, Raha; Tan, Wen Siang; Ali, Abdul Manaf; Yusoff, Khatijah (2009)
The phosphoprotein (P) of paramyxoviruses plays a central role in the viral genome RNA replication and transcription. In genome replication, the P binds to the unassembled nucleocapsid (NP0) and activates it to encapsidate the newly synthesized viral genomic RNA. P also plays a supplemental role in genomic RNA synthesis by binding to the ribonucleoprotein template which composed of genomic RNA in complex with the NP. In this study, the P region of Newcastle disease virus (NDV) that binds to assembled NP (NPNC) was mapped. A total of 18 N- and C-terminally truncated P mutants were synthesized by in vitro translation in rabbit reticulocytes containing [35S]-methionine. These radiolabelled mutants were mixed with the purified full-length NP and determined their interactions in immunoprecipitation assay and protein binding assay. Immunoprecipitation assay showed that the region of P that binds to NPNC is located within the internal region of C-terminal half of P, from amino acids 243 to 279. Protein binding assay also showed a similar interactive domain except that the interactive region is slightly bigger (amino acids 224-279). Nevertheless, both assays showed that the Nterminal half and immediate C-terminal end of P is not involved in the binding of P to NPNC.